Bridge clinic implementation of "72-hour rule" methadone for opioid withdrawal management: Impact on opioid treatment program linkage and retention in care. (1st July 2022) - Taylor, Jessica L.; Laks, Jordana; Christine, Paul J.; Kehoe, Jessica; Evans, James; Kim, Theresa W.; Farrell, Natalija M.; White, Cedric S.; Weinstein, Zoe M.; Walley, Alexander Y.
Abstract: Background: Methadone for opioid use disorder (OUD) treatment is restricted to licensed opioid treatment programs (OTPs) with substantial barriers to entry. Underutilized regulations allow non-OTP providers to administer methadone for opioid withdrawal for up to 72 h while arranging ongoing care. Our low-barrier bridge clinic implemented a new pathway to treat opioid withdrawal and facilitate OTP linkage utilizing the "72-hour rule." Methods: Patients presenting to a hospital-based bridge clinic were evaluated for OUD, opioid withdrawal, and treatment goals. Eligible patients were offered methadone opioid withdrawal management with rapid OTP referral. OTPs accepted patients as direct admissions. We described bridge clinic patients who received at least one dose of methadone between March-August 2021 and key clinical outcomes including OTP referral completion within 72 h. For the subset of patients referred to our two primary OTP partners, we described OTP linkage (i.e., attended at least one OTP visit within one month) and OTP retention at one month. Results: Methadone was administered during 150 episodes of care for 142 unique patients, the majority of whom were male (73%), white (67%), and used fentanyl (85%). In 92% of episodes (138/150), a plan for ongoing care was in place within 72 h. Among 121 referrals to two primary OTP partners, 87% (105/121) linked and 58% (70/121) were retained at one month. Conclusions: Methadone administration for opioid withdrawal with direct OTP admission under the "72-hour rule" is feasible in an outpatient bridge clinic and resulted in high OTP linkage and 1-month retention rates. This model has the potential to improve methadone access. Highlights: Barriers to methadone treatment entry at opioid treatment programs (OTP) are high. Underused rules allow methadone administration for withdrawal outside OTP for ≤ 72 h. 72 h rule methadone in a bridge clinic led to high OTP linkage and 1-mo retention. This care model can improve access to methadone under current regulations.